Solid organ injury in blunt trauma abdomen: an etiological evaluation and success rate of non-operative management - M. L., Ramachandra; S. R., Krishna (International Surgery Journal, 2018)
Background: Trauma remains the most common cause of death for all individuals between the ages of 1 and 44 years. 10% of these fatalities are attributable to abdominal injury. The Indian fatality rates for trauma are 20 times that for developed countries. The management of patients with blunt abdominal injury has evolved greatly over the last few decades from complete surgical management historically to present non operative management in most of the cases. In view of increasing number of road traffic accidents, rampant increase in construction work, accidental fall from height, this study is conducted to look into the causes of such incidents and also to strengthen the already established rules of non operative management in cases of blunt trauma abdomen. Methods: This is a prospective study of 53 patients who presented to K. R. Hospital, Mysuru, Karnataka, for management of blunt trauma abdomen over the period of January 2016 to June 2017. Unstable patients with initial resuscitation underwent Focused Assessment Sonography for Trauma. Failed resuscitation with free fluid in abdomen confirmed by FAST immediately shifted to operation theatre for laparotomy and proceed. Hemodynamically stable patients underwent computerized tomography of abdomen. Organ injuries were scaled according to the American Association for the Surgery of Trauma and these patients were managed conservatively after ruling out hollow viscus perforation. Results: Majority of the patients belonged to male sex (85%) and of the age group 21-40 years constituting 58.3% of patients. Road traffic accident was the most common mode of injury which included 35 patients (66%). A total of 19 cases had splenic injury out of which 13 (68.5%) underwent non operative management and 6 (31%) underwent emergency Splenectomy. liver injury was present in 15 patients and all were managed conservatively. In total non operative management was done in 73.5% of cases and surgical management was done in 26.5% of cases. Conclusions: The presence of free fluid with organ injury always does not mandate laparotomy. Patient selection, early diagnosis and repeated clinical examination and use of appropriate investigations forms the key in non operative management of blunt trauma abdomen. RTA being the most common mode of injury, adequate measures should be taken to prevent road traffic accidents by strict action and traffic norms and citizen education.